Stance Expression in Abstract Section of English Research Articles: How Are Cambodian and International Authors Different? - Thida Or; Chenda Soeurn; Sovann Ly; Voithna Nhean (Journal of English for Specific Purposes in Indonesia, 2025)
Stance is an academic writing trait relating to how writers interact and communicate with their audience through language. This research focuses on the following kinds of stance expressions and sub-classes: boosters,​ hedges, attitude indicators, and self-mentions written by Cambodian and international authors. This study analyzed a corpus of 30 abstracts of the research article using Antconc software and the Hyland (2005) analytical framework model. The abstracts were culled from high-quality papers in the following fields: international journals and Cambodian journals. A qualitative research design was used to explore answers to three research questions: (1) what types of stance expressions are employed in Cambodian and foreign authors' abstract parts of English research articles? (2) what do Cambodian and International authors employ the sub-category devices in their research abstracts? (3) what are the differences in stance expression of English research abstracts written by Cambodian and international authors? The findings of this study indicated that types of four stance expressions were presented in the abstract section of English research papers, with the hedge being the most commonly used among the other subtypes of stances. Within both journals, there is a substantial difference in the use frequency of the attitude self-mention and markers categories; however, there is none for hedges and boosters. This analysis suggested Cambodian authors seek the understanding of stance expression and consider following international authors as a model for writing stance expression in their research article abstract.